2013
DOI: 10.1016/j.mrgentox.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic damage in the blood lymphocytes of astronauts: Effects of repeat long-duration space missions

Abstract: Human missions onboard the International Space Station (ISS) are increasing in duration and several astronauts have now participated in second ISS increments. The radiation environment in space is very different from terrestrial radiation exposure and it is still unclear if space flight effects and radiation from repeat missions are simply additive, which potentially confounds the assessment of the cumulative risk of radiation exposure. It has been shown that single space missions of a few months or more on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 14 publications
0
35
0
1
Order By: Relevance
“…Figure S1 in the supplemental material shows the same phylogenic data represented in a phylogram. As it has been suggested previously that genetic consequences resulting from irradiation exposure during time in space may manifest as insertions and deletions (indels) over point mutations (2830), we analyzed ISSFT-021, IF1SW-F4, and CEA10 and averages from all sequenced isolates included in this study against the reference genome (Af293) and found no obvious enrichment for indels in the ISS isolates (see Fig. S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Figure S1 in the supplemental material shows the same phylogenic data represented in a phylogram. As it has been suggested previously that genetic consequences resulting from irradiation exposure during time in space may manifest as insertions and deletions (indels) over point mutations (2830), we analyzed ISSFT-021, IF1SW-F4, and CEA10 and averages from all sequenced isolates included in this study against the reference genome (Af293) and found no obvious enrichment for indels in the ISS isolates (see Fig. S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 94%
“…S2 in the supplemental material), suggesting that life aboard the space station was not accompanied by an accumulation of mutations presumably from enhanced exposure to irradiation and microgravity; however, since the proper terrestrial control strains do not exist for ISSFT-021 and IF1SW-F4, we cannot determine/quantify mutations that may have accumulated during time aboard the ISS. Interestingly, previous data suggest that DNA damage resulting from time aboard the ISS may favor chromosomal aberrations and large deletions over point mutations (2830), a conclusion that may have been fueled by studies that reported finding no detectable mutations from time in space, although these experiments utilized experimental setups that would favor detection of point mutations over large genetic lesions, or the studies were possibly too short in duration for mutations to accumulate (44). Sequence analysis with ISS A. fumigatus strains suggested that there is no enrichment for any type of mutation we could identify through our resequencing-based mapping approach, namely, indels, in comparison with Af293 (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This argument suggests an approximate doubling of the bystander contribution of 1.1 per 100 cells due to fractionation, which leads to an estimate of ;2.7 aberrations per 100 cells and is consistent with the increase observed in the 30 min to Our results for human lymphocytes at low doses do not provide evidence for NTE contributing to the induction of chromosomal aberrations. Chromosomal aberrations are used to monitor astronauts' radiation exposures while on the International Space Station (33,34), and our lack of a bystander effect in lymphocytes provides support for the accuracy of this assay. This could be due to the fact that in contrast to irradiation of confluent fibroblasts, lymphocytes irradiated in blood tubes have reduced modes of intercellular effects compared to fibroblasts.…”
Section: Discussionmentioning
confidence: 95%
“…Other factors to be considered include smoking history which effects lung, esophagus, oral cavity, bladder and several other cancers, and reproductive history which can impact the risk of breast and other cancers in women [29]. The collection of biodosimetry and biomarker data prior to flight and at multiple time points over several years post-flight [47] would aid in understanding of causation, especially for repeat ISS flyers.…”
Section: Discussionmentioning
confidence: 99%